Preliminary Study on the Production of Extracellular Protease from a Newly Isolated Bacillus sp. (No.1) and the Physical Factors Affecting Its Production - Abdul Razak, Che Nyonya; Tang, S. W.; Basri, Mahiran; Salleh, Abu Bakar (Universiti Putra Malaysia Press, 1997)
A thermophilic bacterium isolated from a dumping ground in Sri Petaling, Kuala Lumpur, identified as Bacillus sp. (No.1), was able to grow at 600C and showed proteolytic activity on skim milk agar. The protease production by this bacterium and some physical factors affecting its production were investigated. Significant protease activity was detected in the basal medium after incubation for 16 h at 50°C with shaking at 200 rpm and reached its peak after 30 h. The protease production coincided with the late exponential or early stationary phase of bacterial growth and corresponded with the sporulation of this bacterium. The optimum pH, agitation rate and temperature for protease production by Bacillus sp. (No.1) were pH 8, 150 rpm and 50°C, respectively.